FKBP5 genetic variants are associated with respiratory- and sleep-related parameters in Chinese patients with obstructive sleep apnea - Wang, Anzhao; Wei, Zhicheng; Yuan, Haolin; Zhu, Yaxin; Peng, Yu; Gao, Zhenfei; Liu, Yuenan; Shen, Jinhong; Xu, Huajun; Guan, Jian; Yin, Shankai; Liu, Feng; et al. (Frontiers in Neuroscience, 2023)
Introduction Obstructive sleep apnea (OSA) has been associated with psychiatric disorders, especially depression and posttraumatic stress disorder (PTSD). FKBP5 genetic variants have been previously reported to confer the risk of depression and PTSD. This study aimed to investigate the association of single nucleotide polymorphisms (SNPs) in the FKBP5 gene with OSA and OSA-related quantitative traits. Methods Four SNPs within the FKBP5 gene (rs1360780, rs3800373, rs9296158, rs9470080) were genotyped in 5773 participants with anthropometric and polysomnography data. Linear regression and logistic regression analyses were performed to evaluate the relationship between FKBP5 SNPs and OSA-related traits. Binary logistic regression was used to assess the effect of SNPs on OSA susceptibility. Interacting genes of SNPs were assessed based on the 3DSNP database, and expression quantitative trait loci (eQTL) analysis for SNPs was adopted to examine the correlation of SNPs with gene expression. Gene expression analyses in human brains were performed with the aid of Brain Atlas. Results In moderate-to-severe OSA patients, all four SNPs were positively associated with AHIREM, and rs9296158 showed the strongest association (ß = 1.724, p = 0.001). Further stratified analyses showed that in men with moderate OSA, rs1360780, rs3800373 and rs9470080 were positively associated with wake time (p = 0.0267, p = 0.0254 and p = 0.0043, respectively). Rs1360780 and rs3800373 were 28 and 29.4%more likely to rate a higher ordered MAI category (OR (95% CI) = 1.280 (1.042 – 1.575), p = 0.019; OR (95% CI) = 1.294 (1.052 – 1.592), p = 0.015, respectively). Rs9296158 and rs9470080 increased the risk of low sleep efficiency by 25.7 and 28.1% (OR (95% CI) = 1.257 (1.003 – 1.575), p = 0.047; OR (95% CI) = 1.281 (1.026–1.6), p = 0.029, respectively). Integrated analysis of eQTL and gene expression patterns revealed that four SNPs may exert their effects by regulating FKBP5, TULP1, and ARMC12. Conclusion Single nucleotide polymorphisms in the FKBP5 gene were associated with sleep respiratory events in moderate-to-severe OSA patients during REM sleep and associated with sleep architecture variables in men with moderate OSA. FKBP5 variants may be a potential predisposing factor for sleep disorders, especially in REM sleep.